Hyper‐selectivity of immigrants and generational differences in occupational status: Evidence for Asian groups in Australia. Issue 1 (14th June 2021) - De Alwis, Sheruni; Parr, Nick; Guo, Fei
Abstract: This paper explores the occupational status of immigrant birthplace‐generation groups in Australia, a country which emphasises skills in immigrant admissions. Using 2016 data, the occupational statuses of the first, 1.5, and second generations of Australia's China, India, Malaysia, Philippines, and Vietnam birthplace‐generation groups are compared to those for the main English‐speaking countries, all other countries, and third‐ and above‐generation Australians. The results show that the occupational status of the 1.5‐ and second‐generation Asian groups considered generally exceed that for their first generation counterparts and invariably exceed that for third‐ and above‐generation Australians, even after controlling for a range of confounding factors. For most Asian groups, the 1.5 generation's occupational status exceeds that of the second generation. Modification of the 'segmented assimilation' hypothesis to incorporate a new category of 'hyper‐selective differentiation' is proposed to capture the extraordinary upward occupational mobility of most 1.5‐ and second‐generation Asian groups in Australia.